Development of a water management system to improve management and scheduling of water orders in Imperial Irrigation District - Young, Greg, author; Thoreson, Bryan, author; Baro, Alpha, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
Over the last decade, distribution system operations at Imperial Irrigation District (IID) have evolved, driven by internal water-user needs and external pressures to conserve water. The result is increasing flexibility in deliveries to water users. However, associated distribution system operations have resulted in fluctuating water levels, varying delivery flows, increasing canal over toppings and other issues - leading to the need for fine-tuning of the ordering, tracking, and delivery processes. IID's goal is to manage water flowing from the Colorado River to the delivery gate in a single, integrated environment. Presently, management of water from the river to the farms is performed by series of processes that are part digital and part paper. While the system works well relative to current needs, system improvement and integration is needed to facilitate higher levels of service and efficiency and to meet increasing requirements for operational flexibility. This improved system is referred to as the Water Management System (WMS). This paper provides an overview of the functional requirements for the WMS, the anticipated software and hardware architecture, and the process that will be used to ensure IID staff's full ownership of the system.
Management and scheduling of water orders
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."